(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Rajasthan High Court observed that a death is always traumatic. More so, when it is attributable to the medical negligence or otherwise, this could have been eschewed with a degree of requisite care. But, aside of the merits of the findings of MCI on medical negligence of the petitioner, the issue which has been agitated in the writ petition is with regard to the manner in which proceedings were taken against the petitioner for his alleged medical negligence. In the present case, issues of lack of informed consent and medical negligence on the part of petitioner and two other doctors were raised by complainant. He filed a complaint against them with Rajasthan Medical Council (RMC) which was dropped after inquiry. He again made complaint with RMC which was kept pending for almost 6 years. In the meantime, he requested MCI to transfer complaint from RMC to MCI. After that, RMC dismissed the complaint after inquiry. No appeal was filed by complainant against this order to MCI under clause 8.8 of Regulations, 2002. In spite of that, MCI instructed Principal, Sawai Man Singh Medical College, Jaipur, to order an inquiry and submit report. Later, report was forwarded to ethics committee mentioning no negligence on the part of doctors. On later date, MCI found petitioner guilty of medical negligence. MCI passed order directing striking off the petitioner’s name from Indian Medical Register for a period of 18 months. Same order was also passed by RMC. It was challenged by petitioner in Rajasthan High Court (RHC) on various grounds. Later, High Court quashed and set aside the order passed by MCI and RMC.